Something in the air: Toxic pollution in and around U.S. prisons - Toman, Elisa L. (Punishment & society, 2023)
Toxic chemicals are released into land, air, and waterways daily. Exposure to such chemicals, however, is not equally distributed across the U.S. It is well documented that communities without agency and capital, typically economically and socially disadvantaged, are those that suffer the brunt of the impacts of a polluted environment. These impacts can have both acute and chronic health consequences, leading to lower life expectancy, higher cancer rates, and compromised immune systems. Emerging qualitative work indicates that incarcerated persons – individuals who have no agency to leave their environment – are disproportionately affected by our polluting practices. This study argues that environmental regulations across the country allow polluting industries to poison confined populations. Nationwide data from the Environmental Protection Agency's Toxic Release Inventory is used to examine if industries geographically closer to correctional facilities emit greater amounts of toxic chemicals. Regional differences are examined as well. Results identify a pattern of harm – incarcerated persons who already have compromised health are also exposed to high levels of toxic chemicals.